MOTIVATION FOR WORKING TOWARDS A NEW ERA OF ORGANIZATION OF AIR TRAFFIC ENGINEERING BUREAU EMPLOYEES OF AERONAUTICAL RADIO OF THAILAND CO., LTD. - Insiri , Suthep; Chantarotorn, Nattawut (Journal of Educational Review Faculty of Education in MCU, 2024)
This research aims to 1) study the level of motivation to work towards a modern organization of air traffic engineering staff and 2) study different personal factors that affect the motivation to work towards a modern organization of air traffic engineering staff of Aeronautical Radio of Thailand Co., Ltd. The research group consisted of 137 air traffic engineering staff of Aeronautical Radio of Thailand Co., Ltd. The statistics used for data analysis were frequency, percentage, mean, standard deviation, chi-square, and Pearson correlation coefficient. The research results showed that 1) the overall level of motivation of air traffic engineering staff of Aeronautical Radio of Thailand Co., Ltd. was at a high level. The highest motivating factor was 1 aspect: work achievement, and 4 aspects were at a high level: recognition, nature of work, responsibility, and career advancement. The overall supportive factors were at a high level in 5 aspects: policy and administration, governance and command, interpersonal relations, work environment, salary and benefits, and 2) the results of hypothesis testing, motivation to work of employees in the Air Traffic Engineering Department, Aeronautical Radio of Thailand Co., Ltd., classified by personal factors, found that employees with different genders had no different motivation to work, therefore the hypothesis was rejected. Employees with different ages, education levels, positions, length of employment, and monthly income had different motivations to work, therefore the hypothesis was accepted.